2012
DOI: 10.1021/jf303327n
|View full text |Cite
|
Sign up to set email alerts
|

Release Behavior and Stability of Encapsulated d-Limonene from Emulsion-Based Edible Films

Abstract: Edible films may act as carriers of active molecules, such as flavors. This possibility confers to them the status of active packaging. Two different film-forming biopolymers, gluten and ι-carrageenans, have been compared. D-Limonene was added to the two film formulations, and its release kinetics from emulsion-based edible films was assessed with HS-SPME. Results obtained for edible films were compared with D-limonene released from the fatty matrix called Grindsted Barrier System 2000 (GBS). Comparing ι-carra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The essential oils and d-limonene are liquids in their natural form and have several limitations to be used in the beverages industry. Some authors have reported that these compounds are susceptible to oxidation, through which they lose their flavor characteristics (Kaushik & Roos, 2007;Marcuzzo et al 2012). Therefore, the encapsulation of flavors in carrier matrices obtained by spray drying can deliver pure lasting flavors and enrich and fortify foods and beverages without degradation of actives (Aguiar et al 2012;Jafari et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils and d-limonene are liquids in their natural form and have several limitations to be used in the beverages industry. Some authors have reported that these compounds are susceptible to oxidation, through which they lose their flavor characteristics (Kaushik & Roos, 2007;Marcuzzo et al 2012). Therefore, the encapsulation of flavors in carrier matrices obtained by spray drying can deliver pure lasting flavors and enrich and fortify foods and beverages without degradation of actives (Aguiar et al 2012;Jafari et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This work presents a systematic characterization of the Pluronic PE9400 at the air-water and limonene-water interfaces. Limonene is an interesting bio-derived solvent which has been used in food [31][32][33] and pharmaceutical applications [34], and in the formulation of biocompatible microemulsions [35]. Furthermore, limonene is an interesting candidate to be used as (bio)solvent, replacing more polluting solvents such as hexane or xylene [36] in agrochemical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…0.1À1000 Fabra et al, 2012;Marcuzzo et al, 2012;Syamaladevi et al, 2012. Transmission electron microscopy (TEM)…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…0.02À1.2 Choi et al, 2009;Shah et al, 2012. Others NA NA 100À1000 Ma et al, 2013;Marcuzzo et al, 2012;Patel et al, 2013;Penbunditkul et al, 2012;Yeo et al, 2005.…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 99%
See 1 more Smart Citation